Role of promyelocytic leukemia protein (PML) in the interferon-sensitivity of lymphocytic choriomeningitis virus (2001)
ABSTRACT: Lymphocytic choriomeningitis virus (LCMV) induces type I interferon (alpha and beta interferon [IFN-α and IFN-β]) upon infection and yet is sensitive to the addition of type II interferon (gamma interferon [IFN-γ]) to the culture media. This sensitivity is biologically important because it correlates inversely with the ability of certain LCMV strains to persist in mice (D. Moskophidis, M. Battegay, M. A. Bruendler, E. Laine, I. Gresser, and R. M. Zinkernagel, J. Virol. 68:1951-1955, 1994). The cellular oncoprotein PML is induced by both IFN-α/β and IFN-γ, and PML binds the LCMV Z protein and becomes redistributed within cells from nucleus to cytoplasm upon LCMV infection. In the present study, increased PML expression results in diminished LCMV replication, implicating PML in the IFN sensitivity of LCMV. Virus production in PML −/− murine embryonic fibroblasts (MEF) exceeds virus production in PML +/+ MEF, and this difference is exacerbated by IFN treatment that upregulates PML expression. IFN-γ also diminishes LCMV production in PML −/− cells; therefore, viral IFN sensitivity is not entirely due to PML. Both viral mRNA production and viral protein production decrease as PML expression increases. Here we propose that PML reduces LCMV transcription through its interaction with the Z protein.